Glutathione S-transferase M1 (GSTM1) Polymorphism and Childhood Acute Lymphoblastic LeukemiaRisk: A Case-Control Study- Khartoum-Sudan(2014-2017) - Hassab Elgawi, Marwa Hamed; Ibrahim, Ibrahim Khider (Gezira Journal of Health Sciences, 2019)
Background: Glutathione S-transferase (GST) enzyme levels are associated with the risk of many cancers, including hematological malignancies. Conflicts in the published results and the absence of similar in-depth studies in Sudan prompted us to perform the present investigation to detect a possible association between polymorphisms at the GSTT gene and susceptibility to develop ALL in a Sudanese population. Objectives:  This study aimed to investigate the relationships between GSTT1 polymorphisms and the risk of acute lymphoblastic leukemia (ALL). Materials and Methods: A total of 40 patients with ALL and 30 control subjects were enrolled in this case control study. Blood samples were collected from all patients and controls in EDTA. Genomic DNA was extracted from all blood samples using salting out method. Genotyping for detection of GSTT1 polymorphism was performed for both patients and controls using an allele-specific PCR Results: GSTT1 null genotype was detected in 53% of ALL patients (21/40) and in 17% (5/30) of the control group, and GSTT1 present genotype was detected in 47% (19/40) in ALL patients group and in 83% (25/30) of the control group. We reported that there is an association between the GSTT1 null genotype and ALL risk (OR= 5.5, 95% CI= 1.7616 to 17.3364; P = 0.003). Conclusion: This study reported that there was an association between the GSTT1 null genotype and ALL risk(OR=5.5, 95% CI=1.7616 to 17.3364; P=0.003) appear also to have an influence in the development of ALL.